Economic analysis of a high-pressure gas network construction using the excavation and trenchless methods - Kramża, Adam; Piechurski, Florian (Instal, 2021)
The construction, extension and modernization of high pressure gas transmission and distribution pipelines is crucial for the national and international gas distribution system. Investments in the natural gas transport sector involve large amounts of money, materials and working hours. The subject of this work is the analysis of the high pressure gas pipelines construction by the open excavation and trenchless method in economic terms. The study presents a description of the construction methods including materials, technological devices and work organization at the construction site. The analysis presents construction projects of the high-pressure gas pipeline DN200 with a length of about 1814 m in Z and DN500 with a length of about 312 m in M. Based on the technical conditions and design requirements for the investment, lists of materials and raw materials, construction equipment and machinery as well as the required man hours were presented for the construction in trench and trenchless technology. After presenting the construction costs and factors that significantly affect the deadline for gas pipelines both construction systems were compared. This work discussed the relationship between the technology for building a high pressure gas pipeline depending on the prevailing field conditions, design assumptions and the length of the pipeline section, and the efficiency and costs of carrying out the works. The significance of these factors has been raised to choose a more economical construction technology at the investment planning and design stage.
Keywords: gas network; excavation construction; trenchless construction; construction cost analysis